AB1029 Allopurinol and cardiovascular outcomes in patients with ischaemic heart disease (ALL-HEART) study: baseline characteristics of the randomised patient population. (12th June 2018) - Mackenzie, I.; Ford, I.; Hawkey, C.; Begg, A.; Taggar, J.; Struthers, A.; Wei, L.; Avery, A.; Walker, A.; Duce, S.; Barr, R.; Dumbleton, J.; et al.
Abstract : Background: Allopurinol is licensed for the prevention of gout. In recent years, several studies have suggested that allopurinol may have beneficial effects on cardiovascular parameters. The ALL-HEART study is a large outcome trial designed to investigate whether allopurinol improves cardiovascular outcomes in patients with ischaemic heart disease[. 1 It is a multicentre, controlled, prospective, randomised, open-label, blinded endpoint trial of allopurinol (up to 600 mg daily) versus no treatment added to usual care in patients aged 60 and over with ischaemic heart disease. Patients are followed up by electronic record-linkage and annual questionnaires. Patient recruitment to the trial started in 2014 and completed in 2017 and follow-up is ongoing. Objectives: To describe the baseline characteristics of the patients randomised into the ALL-HEART study. Methods: The primary endpoint of the ALL-HEART study is the composite of non-fatal myocardial infarction, non-fatal stroke or cardiovascular death. Secondary outcomes include all-cause mortality, quality of life and cost-effectiveness of allopurinol. The study will end when 631 adjudicated primary outcomes have occurred. Results: 5938 patients from the UK have been randomised into the ALL-HEART study. The mean age at randomisation was 72.1±6.8 (SD) years. 75.2% of participants are male. 56.5% are former smokers and 9.4% current smokers. Mean systolic blood pressure was 133±18 mmHg and mean diastolic blood pressure 72±11 mmHg. Mean body mass index was 28.9±5.3 kg/m 2 . The average duration of ischaemic heart disease was 11.5±7.9 years. 47.4% of participants had a history of previous myocardial infarction, 64.2% a history of angina, 56.4% a history of coronary revascularisation and 69.3% had other evidence of ischaemic heart disease. 57.6% had a history of hypertension. 3.9% had a history of previous cerebrovascular accident, 7.6% of peripheral arterial disease, 21.8% of diabetes mellitus, 8.9% of chronic obstructive pulmonary disease and 5.2% of heart failure. Conclusions: This large ongoing trial will determine whether allopurinol improves major cardiovascular outcomes in patients with ischaemic heart disease. Reference: [1] Mackenzie IS, Ford I, Walker A, et al. Multicentre, prospective, randomised, open-label, blinded endpoint trial of the efficacy of allopurinol therapy in improving cardiovascular outcomes in patients with ischaemic heart disease: protocol of the ALL-HEART study. BMJ Open2016;6:e13774. doi:10.1136/bmjopen-2016-013774. Acknowledgements: This study is funded by the National Institute for Health Research, Health Technology Assessment programme (http://www.nihr.ac.uk) (HTA 11/36/41). The study is sponsored by the University of Dundee and NHS Tayside. The study is supported by the Scottish Primary Care Research Network, Support for Science in Scotland and the NIHR Local Clinical Research Networks. Disclosure of Interest: None declared